Perbandingan Stabilitas Obat Racikan Yang Dipreparasi Menggunakan Mortir Dan Tablet Crusher Di Apotek Sarana Pelayanan Kesehatan Primer - Jaya, Made Krisna Adi (Jurnal Farmasi Udayana; Vol. 9, No. 2, Tahun 2020DO - 10.24843/JFU.2020.v09.i02.p06, 2020)
Background: Drugs crushed using mortar is indeed already assessed according the procedure and maintained stability of the cure. But this process requires a relatively long that made some pharmacies preparing medications using a tablet crusher machine. There is a possibility of crushed using a tablet crusher will reduce the stability of certain types of drugs if direct contact with the metal blender machine. Purpose: the variable examined was the stability of the region, namely drug comparison of levels of a drug that dipreparasi uses a tablet crusher and mortar in the primary health care facility pharmacies. Methods: UV-VIS spectrophotometry. Results: the maximum wavelength of klorfeniramine maleate acquired was 261.5 nm and paracetamol is 247.7 nm. % recovery of klorfeniramine maleate raw is ± 2.8% whereas 99.82 on paracetamol is 2.09% ± 100.17. The result of the calculation precision value was obtained by tests at on klorfeniramine maleate is 0.76% whereas on paracetamol is 1.13%. LOD and LOQ of klorfeniramine maleate is 3.20 ± 0.05 and 0.15 ± 9.7 while the LOD and LOQ of paracetamol is 0.38 ± 0.22 and 1.16 ± 0.56. Preparation of comparative test results time crushed with a levels has been made aware that the value of significance test of the Mann Whitney absence of difference levels of drugs that are dipreparasi using mortars and tablet crusher. Conclusion: Drug Crushed with tablet crusher and with mortar does not have the difference statistically. Keyword: blender, crusher, mortars, stability